Acupuncture for restless legs syndrome: A systematic review and meta-analysis protocol - Huang, Kaiyu (Medicine (Baltimore), 2020)
BACKGROUND: Restless legs syndrome (RLS) is a neurological disorder that causes an irresistible urge to move the legs. An increasing number of studies have been published in recent years to support the effectiveness of acupuncture for RLS. We will conduct a comprehensive systematic review and meta-analysis to evaluate the evidence of randomized controlled trials for acupuncture treatment of RLS. METHODS: The following electronic databases will be searched: PubMed, Embase, Web of Science, Cochrane Library, the China National Knowledge Infrastructure, Chinese Biomedical Literature Database, and China Science and Technology Journal Database. The range of publication time will be from the inception of the database to September 2019. Two reviewers will independently conduct article selection, data collection, and risk of bias evaluation. Any disagreement will be resolved by discussion with the third reviewer. Review Manager Software 5.3 will be used for meta-analysis. The Cochrane risk of bias tool will be used to assess the risk of bias. RESULTS: This study will provide a high-quality evidence to assess the effectiveness and safety of acupuncture for RLS. CONCLUSIONS: This systematic review will explore whether acupuncture is an effective and safe intervention for RLS. REGISTRATION: PROSPERO CRD42019148948.